Targeting mitochondrial quality control of T cells: Regulating the immune response in HCC - Xia, Yixue; Gao, Binghong; Zhang, Xue (Frontiers in Oncology, 2022)
Most of the primary hepatocellular carcinoma developed from Virus Hepatitis including Hepatitis B virus, Hepatitis C Virus, and Nonalcoholic Steatohepatitis. And T cells play a crucial role in combating with chronic inflammation and chronic viral infection. However, T cells gradually exhaust under chronic antigen stimulation, which leads to T cell exhaustion in tumor microenvironment, and this exhaustion is associated with mitochondrial dysfunction in T cells. Mitochondria play a key role in altering T cells metabolism modes to achieve desirable immunological responses, and the processes by which mitochondria maintain quality control (MQC) promote metabolism regulation under the microenvironment. Although immune checkpoint inhibitors have been widely used in clinical practice, there are some limitations in the therapeutic effect, combining immune checkpoint inhibitors with targeting mitochondrial biogenesis may enhance cellular metabolic adaptation and reverse the exhausted state. At present, several studies on mitochondrial quality control in HCC have been reported, but there are gaps in the regulation of immune cell function by mitochondrial metabolism, especially the modulating of T cell immune function. This review summarizes and discusses existing studies on the effects of MQC on T-cell populations in liver diseases induced HCC, it would be clued by mitochondrial quality control events.